Integrating Artificial and Human Intelligence in Complex, Sensitive Problem Domains: Experiences from Mental Health - Choudhury, Munmun De; Kiciman, Emre (AI Magazine, 2018)
This article presents a position highlighting the importance of combining artificial intelligence approaches with human intelligence, in other words, the involvement of humans. To do so, we specifically focus on problems of societal significance, stemming from complex, sensitive domains. We first discuss our prior work across a series of projects surrounding social media and mental health, and identify major themes for which augmentation of AI systems and techniques with human feedback has been and can be fruitful and meaningful. We then conclude by noting the implications, in terms of opportunities as well as challenges, that can be drawn from our position, both relating to the specific domain of mental health and for AI researchers and practitioners.